Simulação clínica na residência médica de Obstetrícia e Ginecologia: uma análise no município de São Paulo - Vidotti, Simone Pereira [UNIFESP] (2021)
INTRODUCTION: A new teaching and learning process has been experienced in medical education. In the past, it was based on the usage of traditional methodologies and, in recent years, on a more contemporary model, based on competencies. Within this context, the adoption of methods that encourage effective student participation is being appreciated. They are defined as active methodologies and one of them is the simulation method. OBJECTIVE: this study investigated the use of Simulation in Internal Medical Residency Programs (IMRP) in Obstetrics and Gynecology (OB/GYN) and, more specifically, it comprehended the role attributed by the supervisors to Clinical Simulation (CS) in the training of residents in Gynecology and Obstetrics in the city of São Paulo (SP); it analyzed the use of Clinical Simulation as a teaching strategy in the training of the tocogynecologist during the Medical Residency; it mapped what could facilitate or hinder the insertion of the Clinical Simulation to the Internal Medical Residency Programs of Obstetrics and Gynecology; it also presented suggestions for improving the use of this type of simulation in these programs. METHODOLOGY: for the development of this study was adopted a qualitative, cross-sectional, exploratory, and descriptive approach. Partially structured interviews were conducted with ten supervisors from the Medical Residency Programs of Obstetrics and Gynecology in the city of São Paulo. The analysis of the interviews was carried out by themes and started from three core concepts: the role of simulation in the Medical Residency Programs of Obstetrics and Gynecology; the context in which the simulations were carried out in these programs; the factors that facilitate and/or hinder the insertion of simulation in programs suggestible to the use of Clinical Simulation. RESULT AND DISCUSSION: regarding the role of simulation in the Obstetrics and Gynecology Medical Residency Programs, in the city of SP, the following categories emerged: a complementary tool for the teaching and learning process; possibility for a safe teaching and learning environment; opportunity to learn from mistakes; support for professional practice committed to patient safety; learning scenario for teamwork; a scenario of reflection on the work process in Gynecology and Obstetrics; favoring decision-making; scenario for evaluative processes in the Medical Residency; and, finally, stimulus for the participation of residents in activities. As for the context of the simulation, it was found: usage in different environments; heterogeneity of insertion of the simulation in the Medical Residency Programs; usage of different types of simulators; and the usage of different strategies to insert the simulation in the curriculum. On the topics that facilitate the usage of Clinical Simulation in the Residency Programs, the following stand out: the Clinical Simulation as part of the institutional project; the existence of a physical structure for teaching; the active involvement of preceptors in the teaching-learning process; and the active participation of residents in the organization of training. As difficulties, the following are mentioned: the inadequate structure for carrying out the Clinical Simulation; the obstacles resulting from public management; the overload of assistance activities; the difficulty in providing training opportunities for all residents in a uniform manner; the distancing between the team that provides the theory and the care practice team; and the absence of private partnerships. FINAL CONSIDERATIONS: the supervisors recognize the Clinical Simulation as a powerful pedagogical tool in the learning process of doctors in Residency Programs of Gynecology and Obstetrics. However, they use the simulation in an incipient way, generally, in the skill training of a medical specialty, which occurs randomly for specific situations. Residents are considered great allies in the organization and development of training with Clinical Simulation. Although some supervisors aim for high-tech mannequins for the development of this type of simulation, it is believed that the main transforming factor is the search for alternatives that only human creativity can provide, which means believing in the human capacity for reinvention, overcoming obstacles, and perseverance to incorporate the use of Clinical Simulation in the Internal Medical Residency Programs of Obstetrics and Gynecology.